Burn Injury Impairs Neutrophil Chemotaxis Through Increased Ceramide. Issue 1 (July 2021) - Beckmann, Nadine; Schumacher, Fabian; Kleuser, Burkhard; Gulbins, Erich; Nomellini, Vanessa; Caldwell, Charles C.
Abstract : ABSTRACT: Infection is a common and often deadly complication after burn injury. A major underlying factor is burn-induced immune dysfunction, particularly with respect to neutrophils as the primary responders to infection. Temporally after murine scald injury, we demonstrate impaired bone marrow neutrophil chemotaxis toward CXCL1 ex vivo . Additionally, we observed a reduced recruitment of neutrophils to the peritoneal after elicitation 7 days after injury. We demonstrate that neutrophil ceramide levels increase after burn injury, and this is associated with decreased expression of CXCR2 and blunted chemotaxis. A major signaling event upon CXCR2 activation is Akt phosphorylation and this was reduced when ceramide was elevated. In contrast, PTEN levels were elevated and PTEN-inhibition elevated phospho-Akt levels and mitigated the burn-induced neutrophil chemotaxis defect. Altogether, this study identifies a newly described pathway of ceramide-mediated suppression of neutrophil chemotaxis after burn injury and introduces potential targets to mitigate this defect and reduce infection-related morbidity and mortality after burn. Abstract : Supplemental Digital Content is available in the text